Psychological Well-Being in Early Childhood in Memorizing the Qur'an - Eka Meitya P. Akase (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to describe the psychological well-being experienced by early childhood in memorizing the Qur'an. This study is included in qualitative research using a phenomenological approach to early childhood who memorize the Qur'an. Data collection techniques through observation, interviews and documentation. Then analyze the data by collecting data, reducing, presenting, and drawing conclusions. Based on that, the researcher after collecting data, reducing, then concluded that in memorizing the Qur'an, early childhood obtains psychological well-being through learning with asatidz and friends with the easy and fun talaqqi method so that they are happy when memorizing the Qur'an. In addition, support from family and the environment also affects their psychological well-being, especially in memorizing the Qur'an. Early childhood with psychological well-being can provide peace and good growth and development, especially in forming characters that are in accordance with the teachings of the Qur'an.